Analysis of Law Enforcement Components in Human Trafficking Cases in Indonesia - Noor Rahmad; Annisa Dwi Rahma Septiani (Sharia Faculty, Kiai Haji Achmad Siddiq State Islamic University of Jember, 2026)
This study aims to analyze how factors in law enforcement are applied in handling cases of human trafficking in Indonesia. Human trafficking is a highly complex criminal act, as it involves networks that spread across various regions and parties. This makes the effectiveness of law enforcement very important. This study uses a normative-empirical legal method with an approach in the form of a review of legislation and case studies. The data used was obtained through analysis of legal regulations, court decisions, and reports from institutions such as the Ministry of Women's Empowerment and Child Protection, the Indonesian National Police, and the Indonesian Migrant Workers Protection Agency. The results of the study show that the enforcement of laws against TPPO has not been optimal due to several factors, such as lack of coordination and integrity among law enforcement officials, limited facilities and infrastructure to support investigations, low public awareness of the law, and cultural and social factors that still look down on the role of women and migrant workers. Problems such as corruption, inadequate protection of victims, and a lack of training for officials also exacerbate this situation. The study concludes that effective law enforcement against TPPO can only be achieved through cooperation between legal factors, increased professionalism among officials, and increased institutional and social support for victims.